The war of the worlds - Wells, H. G. (Herbert George), 1866-1946. (Mineola, N.Y. : Dover Publications, 1997)
H.G. Wells' "scientific romance, " published first in serial form and then as a book in 1898, attained perhaps its greatest fame in another form, the infamous realistic 1939 radio broadcast "Invasion from Mars" by Orson Welles. It was also made into an early 1950s science fiction adventure movie. Stover (emeritus, Illinois Institute of Technology) describes Wells' story as "a prophecy of startling originality foreseeing the coming of totalitarianism in the 20th century" (from the introduction). The War of the Worlds is presented as a profoundly ideological philosophical tale, with the world of the Martians representing the progressive future of humanity in a cultural war with our world of tradition and reaction.
Coming of the martians: Eve of the war -- Falling-star -- On horsell common -- Cylinder opens -- Heat-ray -- Heat-ray in the Chobham Road -- How I reached home -- Friday night -- Fighting begins -- In the storm -- At the window -- What I saw of the destruction of Weybridge and Shepperton -- How I fell in the curate -- In London -- What had happened in Surrey -- Exodus from London -- "Thunder Child" -- Earth under the martians: Under foot -- What we saw from the ruined house -- Days of imprisonment -- Death of the curate -- Stillness -- Work of fifteen days -- Man on putney hill -- Dead London -- Wreckage -- Epilogue.
Keywords: Mars (Planet) -- Fiction; Imaginary wars and battles -- Fiction; Martians -- Fiction; Diseases -- Fiction; Earth (Planet) -- Invasions -- Fiction; Space vehicles -- Fiction; Science fiction; War stories; Science fiction